Integrative Analysis of Transcriptome-Wide Association Study and mRNA Expression Profiles Identified Candidate Genes and Pathways Associated With Acute Myocardial Infarction - Chen, Guanzhong; Liu, Liwei; Li, Huanqiang; Lun, Zhubin; Mai, Ziling; Lai, Wenguang; Chen, Enzhao; Zhou, Chunyun; Yu, Sijia; Yang, Junqing; Chen, Shiqun; Chen, Jiyan; et al. (Frontiers in Genetics, 2021)
Background Acute myocardial infarction (AMI), characterized by an event of myocardial necrosis, is a common cardiac emergency worldwide. However, the genetic mechanisms of AMI remain largely elusive. Methods A genome-wide association study dataset of AMI was obtained from the CARDIoGRAMplusC4D project. A transcriptome-wide association study (TWAS) was conducted using the FUSION tool with gene expression references of the left ventricle and whole blood. Significant genes detected by TWAS were subjected to Gene Ontology (GO) enrichment analysis. Then the TWAS results of AMI were integrated with mRNA expression profiling to identify common genes and biological processes. Finally, the identified common genes were validated by RT-qPCR analysis. Results TWAS identified 1,050 genes for the left ventricle and 1,079 genes for whole blood. Upon comparison with the mRNA expression profile, 4 common genes were detected, including HP (PTWAS = 1.22 × 10–3, PGEO = 4.98 × 10–2); CAMP (PTWAS = 2.48 × 10–2, PGEO = 2.36 × 10–5); TNFAIP6 (PTWAS = 1.90 × 10–2, PGEO = 3.46 × 10–2); and ARG1 (PTWAS = 8.35 × 10–3, PGEO = 4.93 × 10–2). Functional enrichment analysis of the genes identified by TWAS detected multiple AMI-associated biological processes, including autophagy of mitochondrion (GO: 0000422) and mitochondrion disassembly (GO: 0061726). Conclusion This integrative study of TWAS and mRNA expression profiling identified multiple candidate genes and biological processes for AMI. Our results may provide a fundamental clue for understanding the genetic mechanisms of AMI.